Vacuum deposition of stoichiometric crystalline PbS films: The effect of sulfurizing environment during deposition. (5th October 2015) - Singh, B P; Kumar, R; Kumar, A; Tyagi, R C
Abstract: Thin film of lead sulfide (PbS) was deposited onto highly cleaned glass and quartz substrates using a vacuum thermal evaporation technique. The effect of the sulfurizing environment on the growth and properties of vacuum-deposited PbS thin film was studied. The ambient sulfurizing environment was created by thermal decomposition of thiourea inside the vacuum chamber during deposition to maintain the stoichiometry and quality of the PbS film. The sulfurizing gas H2 S, produced in the thermal decomposition of the solid sulfur containing thiourea readily combines with the cations (Pb 2+ ) without leaving any anions (S 2− ) at the substrates and also has not produced any excess of sulfur at the substrates. The deposited film was characterized by optical spectroscopy, x-ray diffraction patterns, scanning electron micrographs with energy dispersive analysis of x-rays, and atomic force micrographs. The physical characterization of the deposited PbS film revealed that the surface of film grown in the sulfurizing environment improved and contained more stoichiometric sulfur in comparison to film deposited without the sulfurizing environment.